Examining the distinctiveness of body image and self-related constructs in eating disorders using virtual reality: the role of shape concerns, physical self-worth, and global self-worth - Monthuy-Blanc, Johana; Fortin, Gabrielle; Corno, Giulia; Bouchard, Stéphane (Frontiers in Psychology, 2026)
IntroductionIn Western culture, the female body is commonly socially perceived as an object of evaluation, causing women to frequently evaluate their self-worth based on their physical appearance. Since the last decade, the use of virtual reality (VR) helped clarify the intricate interplay between broader self-related dimensions and dysfunctional eating attitudes and behaviors in women with eating disorders (EDs). The first objective of this study explores the role of body image attitudes (i.e., perceived physical attractiveness, body shape concerns), global self-worth, and physical self-worth in determining visual-perceptual body image representations (i.e., allocentric and egocentric ideal and self-perceived body size) and visual-perceptual body image disturbances (i.e., allocentric and egocentric visual-perceptual body dissatisfaction) in a sample of women with EDs. Additionally, the second objective is to explore the role of body image variables (in terms of attitudes: perceived physical attractiveness, body shape concerns; and in terms of visual-perceptual body image disturbances), global self-worth, physical self-worth, in determining dysfunctional eating attitudes and behaviors (i.e., eating concerns, restraint, and bulimia) in women with EDs.MethodsThe sample involved 96 self-identified female participants. Pearson's bivariate correlations and multiple linear regressions analyses were conducted to investigate the study's objectives. A VR-based figure rating scale was used to perform visual depictive body size estimation tasks in an allocentric and egocentric perspectives.ResultsThe findings indicate that physical self-worth and shape concerns are the primary variables related to visual-perceptual body image dissatisfaction. Shape concerns is also associated with eating concerns.DiscussionThis study emphasizes the critical role of physical self-worth and shape concerns as common variables of interest in relation to both visual-perceptual body image representations and disturbances, as well as shape concerns for dysfunctional eating attitudes and behaviors. These findings clarify the understating of the intricate interplay between body image, broader self-related dimensions, and dysfunctional eating attitudes and behaviors in EDs.